IMPLEMENTATION OF GREEN HUMAN RESOURCE MANAGEMENT AND EMPLOYEES ECO-FRIENDLY BEHAVIOR ON ENVIRONMENTAL PERFORMANCE WITH GREEN INNOVATION AS A MEDIATING VARIABLE AT PTPN 3 KEBUN RAMBUTAN - Kumala Vera Dewi; Indra Welly Arifin; Hastuti Handayani Harahap; Eryani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The type of research used is quantitative research, a research method that places more emphasis on the aspect of objective measurement of social phenomena. The data source used in this research is a primary data source which was directly collected by the researcher from the first source. The data analysis method used by researchers is the Structural Equation Model (SEM) based on Partial Least Square (PLS). The results of the Green Human Resource Management research (X1) do not have a significant influence on the Green Innovation variable (Z). Employees Eco-Friendly Behavior (X2) has a significant influence on the Green Innovation variable (Z). Green Human Resource Management (X1) has a significant influence on the Environmental Performance variable (Y). Employees Eco-Friendly Behavior (X2) has a significant influence on the Environmental Performance variable (Y). Green Innovation (Z) has a significant influence on the Green Innovation (Z) variable. Green Human Resource Management (X1) has a positive effect on Environmental Performance (Y) which is mediated by Green Innovation (Z). Employees Eco-Friendly Behavior (X2) has a positive effect on Environmental Performance (Y) which is mediated by Green Innovation (Z).